Comparison between novel vibrating ceramic MBR and conventional air-sparging MBR for domestic wastewater treatment: Performance, fouling control and energy consumption. (15th September 2021) - Wang, Chuansheng; Ng, Tze Chiang Albert; Ng, How Yong
Highlights: Favourable treatment performance and fouling control were identified in VMBR. PS and PN concentrations of SMP and EPS in VMBR were lower than ASMBR. Reduced biopolymer in SMP & EPS in VMBR helped explain better fouling mitigation. Lower energy consumption and enhanced dewaterability were observed in VMBR. Colloids and biopolymer clusters were significantly reduced in VMBR. ABSTRACT: Two crucial themes emerge from the growing application of MBRs treating domestic wastewater so far: fouling control and energy demand. The significance of in-situ shear-enhanced methods for fouling control in MBRs has been widely acknowledged with air sparging over decades. However, it is still a challenge to develop energy-efficient ways to replace energy-intensive air sparging for effective fouling control during long-term real domestic wastewater treatment. A novel vibrating flat-sheet ceramic MBR (VMBR) was established for investigating the effects of different shear rates on treatment performance, fouling control and specific energy demand compared with air-sparging MBR (ASMBR). Three levels of shear rates with vibration speed of 120, 80, and 40 RPM in the VMBR, versus specific aeration rate of 1.5, 1.0 and 0.5 LPM in the ASMBR were examined as high-, middle- and low-shear phases. Results showed that the VMBR removed over 78.35% TOC, 89.89% COD and 99.9% NH4 -N over three phases, and retarded initial increases in transmembrane pressure to control membrane fouling effectively with average fouling rate around 2.31 kPa/d, 3.59 kPa/d and 10.15 kPa/d, almost 70% lower than the ASMBR in Phase 1, 2 and 3, respectively. Particle size distribution of mixed liquor revealed that colloids and biopolymer clusters were significantly reduced in the VMBR showing less propensity for foulant formation. DOM characteristics further indicated that lower production of polysaccharides and protein (by approximately half in Phases 1 and 2) of SMP and EPS in the VMBR generated lower biopolymer content, promoting better fouling mitigation and enhanced dewaterability compared to the ASMBR. Moreover, the VMBR showed superior energy efficiency for fouling control and could save 51.7% to 78.5% energy of the ASMBR under similar-shear condition. The combination of excellent treatment performance, fouling control and energy efficiency from the VMBR makes this an attractive strategy for future improvement of MBR designs in full-scale application with the potential to replace conventional ASMBR. Graphical abstracts: Image, graphical abstract